Effectiveness of a School-Based Intervention on the Students’ Mental Health After Exposure to War-Related Trauma - El-Khodary, Basel; Samara, Muthanna (Frontiers in Psychiatry, 2020)
Background: After the war conducted against Palestinian civilians in the Gaza Strip, the prevalence of PTSD amongst children and adolescents increased. The counselling department of Ministry of Education in the Gaza Strip applied a counselling programme in the schools in order to alleviate the effect of exposure to war. The aim of the study is to investigate the effectiveness of the counselling programme after exposure to war-traumatic events among Palestinian children and adolescents in the Gaza Strip. Methods: The sample consists of 572 students aged 12-18 years old. Of them 331 (57.9%) were female and 241 (42.1%) were male. Traumatic events were measured by War-Traumatic Events Checklist (W-TECh). Posttraumatic Stress Disorder was measured by the Post-Traumatic Stress Disorders Symptoms Scale (PTSDSS). Anxiety symptoms was adapted from The anxiety symptoms scale, and depression symptoms was measured by Child Depression Inventory. Repeated measures design was employed as the counselling programme was applied in all the schools at the same time. Specifically, the data were collected from the participants before the application of counselling programme and two months later. Results: After applying the school-based counselling programme, the prevalence of PTSD (according to DSM-V) decreased from 57.5% to 45.6% amongst the children and adolescents exposed to war-traumatic events. No gender differences were found regarding the counselling programme. Conclusions: The school-based counselling programme was effective in decreasing the PTSD symptoms amongst children and adolescents after the exposure to war-traumatic events.